Comparison of Static and Dynamic Watchdog Technique to Provide Secure Data Transfer - Gayathri, C; Vadivel, R (International Journal of Computer Sciences and Engineering, 2025)
Wireless network is one of the significant aspects for the roaming users while they travel across the networks transfer of data may done. It provide issues like data attackers were catch the files and they used by their way. Hence user of the network faces the security problems. For this issues watchdog mechanism were provide to monitor the attackers. The watchdog technique is a trust based attacker detection technique which identifies the malicious nodes and its activity in the network is to monitor the nodes within its communication range. The nodes selected as the watchdog nodes are the most trustworthy nodes due to its inherent features like highly stable. For this aspect static and dynamic watchdog techniques were followed, this article provides the comparison between static and dynamic watchdog mechanism to shows which technique provide the best.